Pengaruh Literasi Keuangan Syariah, Interaksi Sosial dan Persepsi Risiko terhadap Minat Investasi Saham Syariah Mahasiswa FEBI UIN Jambi - Selvi Ariani; M. Nazori; Marissa Putriana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
The purpose of this research was to determine the effect of Sharia financial literacy, social interaction, and risk perception on the interest in investing in Sharia stocks among students of the FEBI. This study used a quantitative approach with a causal associative research method with the types and sources of data used were primary and secondary data. Sampling was purposive sampling with a total of 90 students. Data collection utilized a questionnaire and data analysis utilized multiple linear regression. The outcomes revealed that partially Sharia financial literacy, social interaction, and risk perception influenced the interest in investing in Sharia stocks among students studied with a calculated t value < t table and a significance value below 0.05 (P < 0.05). Simultaneously, Sharia financial literacy, social interaction, and risk perception influence the interest in investing in Sharia stocks of students studied with an F-count of 81.233, while F-table is 2.48 (F-count > F-table). The R2 is 0.730, so that 73% of the interest in investing in Sharia stocks of students at the FEBI is influenced by the variables of Sharia financial literacy, social interaction, and risk perception.